The Importance of the Timing of Tocilizumab Administration in Moderate to Severely Ill COVID-19: Single Centered Experience Case series - Eric Daniel Tenda; Setiabakti Andrian; Sedjahtera Albert; Moses M Asaf; Ceva W Pitoyo; Siti Setiati; Imam Subekti (Acta Medica Indonesiana)
One of the main causes of death in COVID-19 is the dysregulation of the host’s immune system which leads to cytokine storm, a potentially fatal systemic inflammatory syndrome. Interleukin 6 (IL-6) is a pro-inflammatory cytokine that is produced in response to infections and tissue injuries and is believed to play a pivotal role in the event of a cytokine storm, as signified by its increase in the process. Considering the role of IL-6 as a pro-inflammatory cytokine in the process of cytokine storm in COVID-19, perceiving IL-6 as a therapeutic target could prove to be promising. Tocilizumab is a monoclonal antibody that competitively inhibits the binding of IL-6 to its receptor (IL-6R). The use of IL-6R blocker is recommended for severe COVID-19 patients in the latest therapeutic guideline published by the World Health Organization (WHO), but the timing of the administration has not been specified. While previous studies about the use of tocilizumab in COVID-19 patients have shown various results, these studies do not emphasize on plasma IL-6 levels when deciding the time of tocilizumab administration. In this case series, we present three patients with moderate to severe COVID-19 infections that receive tocilizumab as an adjunct to the standard of care therapy. This case series introduces the novel idea that the timely use of tocilizumab as signified by plasma IL-6 levels in moderate to severe COVID-19 patients could potentially improve overall clinical condition and increase survival rate.